The Factors Affecting Work Discipline And Motivation An Employee Performance At Aroma Bakery Ayahanda Branch, Medan - Nadya Ulfah; Dewi Nurmalasari Pane; Muhammad Isa Indrawan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
This study was to determine and analyze the effect of work discipline and motivation on employee performance at Aroma Bakery Ayahada Medan Branch. The population in this study was 65 employees. The number of samples in this study was 65 employees or using a saturated sampling technique. Research data were obtained from interviews with employees of the Aroma Bakery Ayahada Medan Branch and distributing research questionnaires. The analysis technique uses multiple linear regression analysis. The results showed that simultaneously work discipline and motivation had a significant effect on employee performance at Aroma Bakery Ayahada Medan Branch. The partial test shows that work discipline and work motivation each have a positive and significant effect on the performance of the employees of Aroma Bakery Ayahada Medan Branch